Implementation of Educational Song Media in Teaching the Sirah of Prophet Muhammad SAW at Al-Muhajirin Qur'anic Learning Center, Alafan District - Vini Nur Zikra (The Indonesian Institute of Science and Technology Research, 2026)
Qur'anic Learning Centers (Taman Pendidikan Al-Qur'an/TPA) play an important role in introducing Islamic values and knowledge to children. One of the essential learning materials delivered in TPA is the sirah (biography) of Prophet Muhammad SAW. However, children often encounter difficulties in understanding and memorizing historical content when it is delivered solely through verbal explanations. This article aims to describe a good practice of implementing educational song media in teaching the sirah of Prophet Muhammad SAW at Al-Muhajirin Qur'anic Learning Center in Alafan District. A descriptive practice-based approach was employed using direct observation and video documentation. The learning activity focused on introducing the names of the Prophet’s children through educational songs. The findings indicate that educational songs increased children's learning interest, participation, and ability to recall learning content. The implementation also created a more enjoyable and interactive learning atmosphere. Educational song media can therefore serve as an effective alternative instructional strategy for Islamic non-formal education settings.